2014
DOI: 10.1016/j.vaccine.2013.11.097
|View full text |Cite
|
Sign up to set email alerts
|

Findings from a hepatitis B birth dose assessment in health facilities in the Philippines: Opportunities to engage the private sector

Abstract: Background Hepatitis B vaccination in the Philippines was introduced in 1992 to reduce the high burden of chronic hepatitis B virus (HBV) infection in the population; in 2007, a birth dose (HepB-BD) was introduced to decrease perinatal HBV transmission. Timely HepB-BD coverage, defined as doses given within 24 hours of birth, was 40% nationally in 2011. A first step in improving timely HepB-BD coverage is to ensure that all newborns born in health facilities are vaccinated. Methods In order to assess ways of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…In our survey, 88% of the children had HB3, similar to the reported coverage of 87% and 88% in 2007 and 2008 respectively, however, the 26% timely birth dose in the survey is higher than the reported 9% and 21% in 2007 and 2008 birth dose coverage, respectively. Reporting of birth dose is problematic in the Philippines because not all facilities report immunization coverage to the EPI, 16 thus the reported birth dose coverage may be lower than it actually is. Prior to 2007, vaccines were mostly available from the private market, but because of the devolved health care set-up some local government units offered HB vaccines to some children thereby increasing the coverage, but this may not have been reported in the EPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our survey, 88% of the children had HB3, similar to the reported coverage of 87% and 88% in 2007 and 2008 respectively, however, the 26% timely birth dose in the survey is higher than the reported 9% and 21% in 2007 and 2008 birth dose coverage, respectively. Reporting of birth dose is problematic in the Philippines because not all facilities report immunization coverage to the EPI, 16 thus the reported birth dose coverage may be lower than it actually is. Prior to 2007, vaccines were mostly available from the private market, but because of the devolved health care set-up some local government units offered HB vaccines to some children thereby increasing the coverage, but this may not have been reported in the EPI.…”
Section: Discussionmentioning
confidence: 99%
“…17 Furthermore, a study conducted in 2011 reported that 8% of hospitals, the majority of which were private facilities, did not provide the birth dose of HB vaccine, nor did they report vaccine coverage to the EPI. 16 Based on these findings, several steps were taken such as the inclusion of the birth dose of HB vaccine in the PhilHealth Newborn Service Package. A previous modelling study suggested that in a setting with 8% chronic hepatitis B prevalence among pregnant women, at least 85% HB3 vaccine coverage and 65% timely HB vaccine birth dose are necessary to achieve the regional goals.…”
Section: Discussionmentioning
confidence: 99%
“…Empowerment of women and equipping them with the knowledge and tools for seeking BDV could increase uptake of interventions. A study of 147 health facilities in the Philippines, a country which introduced BDV in the national programme in 2007, found that the coverage of BDV was lower amongst neonates born in private hospitals compared with those born in government clinics or government hospitals (50%, 90%, 87%, respectively, P = .02) . The low coverage in private sectors included poor knowledge of staff about the BDV, despite this being available for free through the national EPI programme.…”
Section: What Remains To Be Done?mentioning
confidence: 99%
“…In 2015, it is clear that the universal infant vaccination goal has not been met in the Philippines, that HBsAg seroprevalence remains high, and that the Philippines remains hyperendemic. Data collected prior to the implementation of a national vaccine program have shown average prevalence of 12% (in four villages in different provinces from 1979 to 1982), 8.8% (in rural villages in 1986), and a range from 10% in rural communities to 11.8% in Metro Manila (based on 35,623 blood donor samples collected from 1979 to 1980) .…”
Section: Hbsag Seroprevalence In the Philippinesmentioning
confidence: 99%